Antihistamines in Pregnancy - Javad Ghaffari (Mazandaran University of Medical Sciences, 2023)
Allergic disorders are increasing prevalence from decades. Often of allergic diseases such as chronic urticaria in some aspects of quality of life of patients affected. Outdoor and indoor allergens can cause   aggravation of symptoms in allergic patients. H1-antihistamines have been available for decades and those are over-the-counter drugs. The first generation H1-antihistamines have anticholinergic and sedative effects. Basically, their use (H1 blockers) for the routine management of allergic diseases is not recommended.  Second generation H1-antihistamines (bilastine, cetirizine, desloratadine, ebastine, fexofenadine, levocetirizine, loratadine, and rupatadine) have minimally or non-sedating and free of anticholinergic effects. About 10-15% of pregnant women used antihistamine within pregnancy.